A computer-based alarm handling system for process plant - Gary Hoenig (1982)
The modern process plant is characterised by the use of computers for process control. Increasing reliability and diminishing capital investment costs have encouraged the use of process computers as the principal control mechanism. Greater reliability has also led to an increase and change in the tasks assigned to the computer. The relatively rapid advances in process control have understandably resulted in a carry-over of traditional practices which are often inadequate in the present day environment. A notable example of such a practice is the alarm system which is neglected in the literature and is frequently the least satisfactory aspect of a control system. [Continues.]